Comorbidity of long COVID and psychiatric disorders after a hospitalisation for COVID-19: a cross-sectional study. Issue 10 (11th August 2022) - Gasnier, Matthieu; Choucha, Walid; Radiguer, Francois; Faulet, Theo; Chappell, Kenneth; Bougarel, Aurore; Kondarjian, Christian; Thorey, Paul; Baldacci, Antoine; Ballerini, Maryne; Ait Tayeb, Abd El Kader; Herrero, Hugo; et al.
Abstract : Objectives: Long COVID is a major public health issue. Whether long COVID is comorbid with psychiatric disorders remains unclear. Here, we investigate the association between long COVID, psychiatric symptoms and psychiatric disorders. Design: Cross-sectional. Settings: Bicêtre Hospital, France, secondary care. Participants: One hundred seventy-seven patients admitted in intensive care unit during acute phase and/or reporting long COVID complaints were assessed 4 months after hospitalisation for an acute COVID. Main outcome measures: Eight long COVID complaints were investigated: fatigue, respiratory and cognitive complaints, muscle weakness, pain, headache, paraesthesia and anosmia. The number of complaints, the presence/absence of each COVID-19 complaint as well as lung CT scan abnormalities and objective cognitive impairment) were considered. Self-reported psychiatric symptoms were assessed with questionnaires. Experienced psychiatrists assessed Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition-based diagnoses of psychiatric disorders. Results: One hundred and fifteen (65%) patients had at least one long COVID complaint. The number of long COVID complaints was associated with psychiatric symptoms. The number of long COVID complaints was higher in patients with psychiatric disorders (mean (m) (SD)=2.47 (1.30), p<0.05), new-onset psychiatric disorders (m (SD)=2.41 (1.32), p<0.05) and significant suicide risk (m (SD)=2.67 (1.32), p<0.05) than in patients without any psychiatric disorder (m (SD)=1.43 (1.48)). Respiratory complaints were associated with a higher risk of psychiatric disorder and new-onset psychiatric disorder, and cognitive complaints were associated with a higher risk of psychiatric disorder. Conclusions: Long COVID is associated with psychiatric disorders, new-onset psychiatric disorders and suicide risk. Psychiatric disorders and suicide risk should be systematically assessed in patients with long COVID.